MALL in English Language Teaching: The Instructional Model of Integrating Four Skills Facilitated by WhatsApp Application - Fauzi, Iwan (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
With the rapid advancement of information and communication technology (ICT), mobile devices have become increasingly integrated into educational environments. This paper focuses on the use of WhatsApp, a popular messaging app, as a powerful tool for enhancing English language learning by efficiently managing student tasks. It presents an instructional model that incorporates four key English language skills—listening, speaking, reading, and writing—through WhatsApp. This model allows both students and teachers to explore the practicalities, challenges, and achievements associated with using WhatsApp for academic tasks, both during and outside of school hours. The instructional model utilizes WhatsApp in both synchronous and asynchronous modes, offering flexibility in delivering content. Activities for each language skill leverage WhatsApp's capabilities, such as voice notes, text messaging, and multimedia sharing, to enhance the learning experience. This model fosters real-time communication and enables students to practice their language skills even in resource-limited environments. This instructional model implies that WhatsApp is a valuable tool for language teaching, especially for educators with low digital literacy. Its accessibility and flexibility allow for the continuation of education in difficult circumstances. Besides, the instructional model presented provides a framework that can be adapted by English teachers for various learning contexts, supporting both synchronous and asynchronous learning environments.